If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3a + -2) = 50 Reorder the terms: 5(-2 + 3a) = 50 (-2 * 5 + 3a * 5) = 50 (-10 + 15a) = 50 Solving -10 + 15a = 50 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 15a = 50 + 10 Combine like terms: -10 + 10 = 0 0 + 15a = 50 + 10 15a = 50 + 10 Combine like terms: 50 + 10 = 60 15a = 60 Divide each side by '15'. a = 4 Simplifying a = 4
| 2x*2x=4x | | (M+3)x^2+2m(x+1)+3=0 | | sqrt(4x+8)+7=4x | | 16-2(x-1)=x | | 4x-6x-6=3+14 | | 8x+24=6x+40 | | -1/4=1/5b | | 11(x-8)-8=28x-232 | | -1/4=1/5 | | 5x+9=1x+17 | | ln(x)+10x=4 | | 3x/7+4/5=6/7 | | 5(4x+9)= | | -a+b=1800 | | 1/7(7x-6)=-9/2-7/2 | | lnx+10x=4 | | -4[16+(-12)]= | | a+b=7500 | | c^2-2c^2-35= | | 13=w/4-10 | | 4a-3a+2b-8b= | | 14y+12=18 | | 14y+8=12 | | 2.5x+2=-3 | | x^2-32x+54=0 | | 2/7m(4m-18)=12 | | 5(n-3)=35 | | ((1/3)x)-4=(12/7)-((5/6)x) | | 2x(2)+2y(2)=32 | | 2p*3+6= | | 2+-6k+13k*13k+92k*92k*92k= | | 9x-6y=16 |